ANALISIS DAN PERANCANGAN SISTEM INFORMASI PEMASARAN UNTUK MENINGKATKAN PENJUALAN BERBASIS WEB (E-COMMERCE) PADA PT. SINAR REJEKI CEMERLANG - roland dio marwan; Verri Kuswanto (bit-Tech, 2022)
Current developments In today's era, there are still many companies or businesses that still do not use technology. To be able to provide information, internet technology is needed. Accessing the internet can be done anytime and anywhere if a connection is available. All companies will compete with each other to use this technology to market and sell their products so that companies can develop and are able to continue to compete with other companies. efficient, the means is an online marketing and sales system. Based on this situation, the company decided to develop a website like e-commerce. Then a sales information system was made which is similar to an e-commerce website. To train how to market products and the buying and selling process, we can start using the e-commerce web. Making this system will be able to reduce problems that occur between buyers and sellers because it is done by use a system that is usually connected to internet. In addition, buyers can also view detailed product information and understand the product they want to buy. This system is made using the PHP programming language with the Laravel framework. The Laravel framework is a website development that is formed in the PHP language. The results of this research are in the form of designing a web-based online sales system that can also be used to find out detailed product information. respondents, the results of this questionnaire get a percentage value of 95% so it can be concluded that this online sales system can be used, and makes it easier for users.